Studies on mononuclear chelates derived from substituted Schiff base ligands (part 4): Synthesis and characterization of a new 5-hydroxysalicyliden- p-aminoacetophenoneoxime and its complexes with Co(II), Ni(II), Cu(II) and Zn(II) - Canpolat, Erdal; Kaya, Mehmet (My University, 2005)
5-Hydroxysalicyliden-p-aminoacetophenoneoxime (LH) was synthesized starting from p-aminoacetophenoneoxime and 5-hydroxysalicylaldehyde. Complexes of this ligand with Co+2, Ni+2, Cu+2 and Zn +2 salts were prepared. With this ligand, complexes were synthesized using Co+2, Ni+2, Cu+2 and Zn+2 salt with a metal:ligand ratio of 1:2. Their structures were elucidated on the basis of elemental analyses, IR, 1H- and 13C-NMR, electronic spectra, magnetic susceptibility measurements, molar conductivity and thermogravimetric analyses. © TÜBİTAK.
Keywords: Oxime; Schiff bases; Transition metal complexes